Factors influencing post-exercise proteinuria after marathon and ultramarathon races - Wołyniec, Wojciech; Ratkowski, Wojciech; Kasprowicz, Katarzyna; Małgorzewicz, Sylwia; Aleksandrowicz, Ewa; Zdrojewski, Tomasz; Wierucki, Łukasz; Puch-Walczak, Aleksandra; Żmijewski, Piotr; Renke, Joanna (Biology of Sport, 2020)
Post-exercise proteinuria is one of the most common findings observed after short and intensive physical activity, but is observed also after long runs with low intensity. The aim of this study was to analyze factors influencing proteinuria after marathon runs. Two groups of male amateur runners were studied. The results of 20 marathon finishers (42.195 m), with a mean age of 49.3 ± 6.85 years; and 17 finishers of a 100-km ultramarathon with a mean age of 40.18±4.57 years were studied. Urine albumin to creatinine ratio (ACR) was calculated before and after both races. The relationship between ACR and run pace, metabolites (lactate, beta hydroxybutyrate), markers of inflammation (CRP, IL-6) and insulin was studied. The significant increase in ACR was observed after both marathon races. ACR increased from 6.41 to 21.96 mg/g after the marathon and from 5.37 to 49.64 mg/g after the ultramarathon (p<0.05). The increase in ACR was higher after the ultramarathon that after the marathon. There was no correlation between run pace and proteinuria. There was no correlation between ACR and glucose, free fatty acids, lactate, beta-hydroxybutyrate and insulin levels. There was significant negative correlation between ACR and interleukin 6 (IL-6) (r =-0.59, p< 0.05) after ultramarathon. Proteinuria is a common finding after physical exercise. After very long exercises it is related to duration but not to intensity. There is no association between metabolic and hormonal changes and ACR after marathon runs. The role on inflammatory cytokines in albuminuria is unclear.